Sharing and improving project information via digital pens and paper / James Sommerville and Nigel Craig - Sommerville, James; Craig, Nigel (2005)
The collection of information on construction projects still continues to be a process rooted in traditional methods i.e. pen and paper. While the use of IT within the construction industry is becoming widespread as awareness increases, the full drawdown of benefits still leaves room for improvement. Many construction professionals insist 26 on using traditional communication methods to collect and transfer project information. To leverage out these potential benefits, what is required is a process which still uses pen and paper as of its medium while at the same time facilitating the transformation of this information into a digital format, thus affording the organisation the opportunity to translate this information directly into digital project databases/applications. The uptake of a digital pen and paper based approach will allow construction organisations to become more deeply embedded in IT, whilst at the same time allowing the operative the opportunity to collect and transfer project information in a manner they are familiar with i.e. using a pen and paper.